PENGARUH POSISI SAMBUNGAN KONSTRUKSI KAYU TERHADAP DEDAIN PRODUK MEBEL BERBAHAN DASAR KAYU - Bahtiar Rahmat; Desy Mulyosari; Agung Ari Purwanto; Wahyu Widiyanto (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2023)
Wood furniture products were one of the commodities that have a dominant contribution compared to other furniture materials to the Indonesian economy. In furniture products, the connection system was a weak point in the construction, so a detailed analysis was needed regarding the factors that affect the strength of the construction and the effectiveness of the wood connection system. The purpose of this study was to determine the quality of the wood used as outdoor chair material by carrying out several tests to obtain wood density, moisture content, MOR and MOE values and then carrying out impact tests on actual outdoor chair products. The results showed that the teak wood used in the raw material for making the product had a moisture content of 12% with an average density of 0.68 g/cm3. The results of the static flexural strength test showed that the MOE of the tested teak was 107,108 kg/cm2 and the MOR value was 1,018 kg/cm2. The compressive strength value parallel to the fiber is 536 kg/cm2. The teak sample tested was included in strong class II which is quite strong as a raw material for furniture such as outdoor chairs. Analysis of the results of the construction design found that the type of construction used was tenon mortise, cracks at the joints occurred because the tenon was too close to the head of the wood. Based on the product test results, after the product with a new construction design was made, by lowering the tenon mortise position 3 mm from the initial position. The crack that occurs in the product is caused by an error in product construction design and not from the quality of the product raw materials used.